Evaluasi Program Ekstrakurikuler English Club dengan Model CIPP di UPTD SMP Negeri 1 Kupang - Armanjo Kamlasi; Julio Arsanto Meko; Gibson J. K. Sopaba; Yonatan Foeh (Jurnal Riset dan Inovasi Manajemen, 2025)
This study aims to evaluate the implementation of the English Club extracurricular program at UPTD SMP Negeri 1 Kupang using the CIPP evaluation model (Context, Input, Process, Product). The CIPP model was chosen because it provides a comprehensive overview of the various components of the program. The study employs a descriptive qualitative approach, with data collected through observation, interviews, and document analysis. Based on the evaluation results, in terms of context, the program was implemented in response to students' needs to improve their English language skills, supported by school policies and the Education Office. Regarding input, the program is supported by the school principal, program supervisors, and teachers, and is funded through the BOS Fund, although limitations in learning facilities and infrastructure still exist. In the process aspect, the activities are held regularly twice a month after school hours, involving 150 selected students from grades 7 to 9. Internal evaluations are periodically conducted by the school. As for the product aspect, the program has shown a positive impact, as evidenced by improvements in students’ English proficiency, increased self-confidence, and achievements in various English competitions. Overall, the English Club program at UPTD SMP Negeri 1 Kupang is considered successful in achieving its goals and is recommended to be continuously developed and sustained.